Effect of MgO addition on the metallurgical properties of the vanadium-titanium pellet with simulating blast furnace conditions. (20th April 2020) - Zhao, Wei; Chu, Mansheng; Feng, Cong; Wang, Hongtao; Liu, Zhenggen; Tang, Jue; Wang, Wanping
ABSTRACT: MgO addition plays a vital role in improving the quality of pellets. In this study, the effects of MgO addition on the compressive strength, reducibility, reduction swelling characteristics and softening-melting performance of V-Ti pellets were explored systematically with simulating BF conditions. From the results, it can be observed that the compressive strength decreased with increasing MgO due to the formation of magnesioferrite, the restriction of recrystallization-agglomeration of haematite and the decreasing of molten slag. The reducibility of V-Ti pellets improved substantially due to the increase of the porosity. The decreasing of RSI is mainly caused by the decreasing of lattice volume swelling during the transition from MgO·Fe2 O3 to (Mg, Fe)O. In addition, the softening-melting behavior and permeability of V-Ti pellets packed bed was found to be improved with increasing MgO content. In sum, the V-Ti pellets with a MgO content higher than 2.4% exhibits optimum metallurgical properties.